2017
DOI: 10.1002/eap.1576
|View full text |Cite|
|
Sign up to set email alerts
|

Fragmentation increases wind disturbance impacts on forest structure and carbon stocks in a western Amazonian landscape

Abstract: Tropical second-growth forests could help mitigate climate change, but the degree to which their carbon potential is achieved will depend on exposure to disturbance. Wind disturbance is common in tropical forests, shaping structure, composition, and function, and influencing successional trajectories. However, little is known about the impacts of extreme winds on second-growth forests in fragmented landscapes, though these ecosystems are often located in mosaics of forest, pasture, cropland, and other land cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 97 publications
(165 reference statements)
0
33
2
3
Order By: Relevance
“…Forest fragmentation, fires, and windstorms each cause some level of forest disturbance in Amazonia (Brando et al, ; Broadbent et al, ; Chambers et al, ; Haddad et al, ; Negrón‐Juárez et al, ), but if they act synergistically, the impacts on forest structure, dynamics, and carbon stocks could be amplified. Most of the current understanding on the effects of wind disturbances on Amazonia forests derives from studies that quantified the spatial extent of blowdown events using remote sensing imagery (Chambers et al, ; Espírito‐Santo et al, ; Negrón‐Juárez et al, ) or from postdisturbance field inventories, which often lag the windstorm event by many months or years (Marra et al, ; Schwartz et al, ). While these studies have shown that wind disturbance exerts strong influences on the structure and diversity of tropical forests, they often lack mechanistic approaches to understand how forests respond to synergistic interactions between windstorms and other forest disturbances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forest fragmentation, fires, and windstorms each cause some level of forest disturbance in Amazonia (Brando et al, ; Broadbent et al, ; Chambers et al, ; Haddad et al, ; Negrón‐Juárez et al, ), but if they act synergistically, the impacts on forest structure, dynamics, and carbon stocks could be amplified. Most of the current understanding on the effects of wind disturbances on Amazonia forests derives from studies that quantified the spatial extent of blowdown events using remote sensing imagery (Chambers et al, ; Espírito‐Santo et al, ; Negrón‐Juárez et al, ) or from postdisturbance field inventories, which often lag the windstorm event by many months or years (Marra et al, ; Schwartz et al, ). While these studies have shown that wind disturbance exerts strong influences on the structure and diversity of tropical forests, they often lack mechanistic approaches to understand how forests respond to synergistic interactions between windstorms and other forest disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…Amazonia, biomass loss, fire scar, forest degradation, forest dynamics, tree mortality, windstorms spatial extent of blowdown events using remote sensing imagery (Chambers et al, 2013;Espírito-Santo et al, 2014;Negrón-Juárez et al, 2010) or from postdisturbance field inventories, which often lag the windstorm event by many months or years (Marra et al, 2014;Schwartz et al, 2017). While these studies have shown that wind disturbance exerts strong influences on the structure and diversity of tropical forests, they often lack mechanistic approaches to understand how forests respond to synergistic interactions between windstorms and other forest disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…, Schwartz et al. ). Differences in species composition between old‐ and second‐growth forests suggest that second‐growth forests are likely to suffer stronger drought impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Over 70% of all remaining tropical forests in the world are second-growth forests growing on former agricultural or logged lands (Food and Agriculture Organization of the United Nations [FAO] 2010). These regenerating forests differ from old growth in composition, size structure, and spatial configuration in the landscape and thus are expected to respond differently to climate extremes (FAO 2010, Anderson-Teixeira et al 2013, Uriarte et al 2016a, Schwartz et al 2017. Differences in species composition between old-and second-growth forests suggest that second-growth forests are likely to suffer stronger drought impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has also demonstrated significant correlations between wind speed estimates using models (e.g. H*wind, Powell et al 1998), and forest damage determined by spectral shifts before and after the storm (Chambers et al 2007, Zeng et al 2009, Negron-Juarez et al 2014, Rifai et al 2016, Schwartz et al 2017). …”
Section: Introductionmentioning
confidence: 99%